Intragroup contact with other mothers living in the same neighborhood benefits mothers' life satisfaction: The mediating role of group identification and social support. Issue 3 (3rd November 2022) - Seppälä, Tuija; Riikonen, Reetta; Stevenson, Clifford; Paajanen, Paula; Repo, Katja; Finell, Eerika
Abstract: Becoming a mother is often accompanied by a loss of social connections, which can reduce the availability of social support. This can increase maternal stress with negative health outcomes. Therefore, we examined how mothers' social contact with other mothers living in the same neighborhood can form a compensative source of social support and wellbeing. Data was collected from mothers ( N = 443) of a child under school age while visiting the public maternity and child health clinics located in two neighborhoods in Helsinki, Finland. We found that mothers' frequent and positive contact with other local mothers was positively related with their life satisfaction through identification‐based social support. Contact also had a specific indirect effect on life satisfaction through social support. Frequent positive contact with other local mothers can serve to scaffold the emergence of social identification, which in turn unlocks further social support with positive health effects.